2014
DOI: 10.1007/s13524-014-0306-9
|View full text |Cite
|
Sign up to set email alerts
|

Aging in the Context of Cohort Evolution and Mortality Selection

Abstract: This study examines historical patterns of aging through the perspectives of cohort evolution and mortality selection, where the former emphasizes the correlation across cohorts in the age dependence of mortality rates, and the latter emphasizes cohort change in the acceleration of mortality over the life course. In the analysis of historical cohort mortality data, I find support for both perspectives. The rate of demographic aging, or the rate at which mortality accelerates past age 70, is not fixed across co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…' Costa (2012) found that the processes of both selective mortality (producing robust survivors) and physiological scarring (producing frail survivors) can occur; the outcome depends on the age at which the stressor occurred. Zheng (2014) similarly revealed that the two processes are not mutually exclusive. Young-and old-age mortality rates can be positively associated (i.e., indicative of scarring), while young-age mortality rates are simultaneously negatively associated with mortality acceleration (the rate of increase in the mortality rate) late in life (indicative of selective mortality).…”
Section: Examination Of Frailty and Demographymentioning
confidence: 94%
“…' Costa (2012) found that the processes of both selective mortality (producing robust survivors) and physiological scarring (producing frail survivors) can occur; the outcome depends on the age at which the stressor occurred. Zheng (2014) similarly revealed that the two processes are not mutually exclusive. Young-and old-age mortality rates can be positively associated (i.e., indicative of scarring), while young-age mortality rates are simultaneously negatively associated with mortality acceleration (the rate of increase in the mortality rate) late in life (indicative of selective mortality).…”
Section: Examination Of Frailty and Demographymentioning
confidence: 94%
“…These findings support the prediction of increasing prevalence of robust individuals in younger cohorts from technophysio evolution theory and cohort morbidity phenotype theory. All in all, these findings suggest that, although frail individuals are more likely to survive into adulthood in later cohorts due to socioeconomic development and medical advances, which possibly increases the heterogeneity among later cohorts, this selective survival mechanism is not strong enough to reverse the overall reducing mortality variation trend across cohorts due to the continually increasing health capital and decreasing mortality rate at the population level (Zheng 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of historical trends of mortality rates also have found patterns of cohort mortality declines that may have resulted from decreased exposures to physiological risk factors for chronic morbidities such as infection and inflammation (Finch and Crimmins 2004), increased health capital brought about by technophysio evolution (Fogel and Costa 1997), or a combination of these and other factors across birth cohorts (Zheng 2014). Period mortality declines may be attributable to a changing mix of socioeconomic development, lifestyle changes, and medical innovations in each period (Omran 1971; Olshansky and Ault 1986).…”
Section: Temporal Changes In Mortality Ratesmentioning
confidence: 99%
“…Because Han Chinese use a lunar calendar (i.e., animal years) to remember his/her birth date and other important life events -such as marriage -age misreporting is relatively lower than among ethnic minorities in China (Zeng and Gu, 2008;Zeng and Vaupel, 2003). It is also possible that less steep slope of mortality at very old ages in less developed western provinces may be due to mortality selection that dropped those frail persons out, leaving more robust ones in the cohort, a common phenomenon at very old ages in general populations (Zheng, 2014).…”
Section: Discussionmentioning
confidence: 99%